The Effect of Online Learning During Covid-19 Pandemic at SMP Muhammadiyah Al-Amin Sorong City - Rezkiah Hartanti; Dermawan Pribadi Marpaung; Dian Saputra (Journal on Education, 2023)
The Covid-19 pandemic has disrupted the conventional learning process. So a solution is needed to answer this problem. Online learning is one alternative that can overcome these problems. This study was to obtain an overview of the implementation of online learning at SMP Muhammadiyah Al-Amin Sorong City as an effort to suppress the spread of Covid-19 at the junior high school level. The researchers focused on the impact of online learning during the Covid-19 pandemic. The sample of this study was thirteen consisting of 10 eighth grade students, 1 sports teacher, 1 computer teacher, and 1 principal. Data collected through interview techniques. The first is to conduct semi-structured interviews with 10 students who have mobile phones as a tool for participating in online learning. The purpose of this study was to determine the impact felt during online learning during the Covid-19 pandemic. The second conducted interviews with 2 teachers and the principal. The purpose of the interview is to support data from the results of student interviews. The results of this study show that there are positive impact, 7 participants feel that online learning does not interfere with their activities, and 5 participants feel that online learning saves their transportation money, and 5 participants better understand the online learning process, because it is helped by material sources on the internet. While the negative impact, 5 participants felt that the learning process was inefficient, 4 participants considered the learning materials provided could not be understood because of the limited internet connection, and 4 participants thought they had to spend more to buy data packages, as an effort to be able to take online learning.